Exploring the interactions of therapeutic phytochemicals, flavokawain b, pinostrobin and 6-shogaol with human serum albumin: Spectroscopic and molecular docking investigations / Shevin Rizal Feroz - Shevin Rizal, Feroz (2017)
The rhizomes of the plants of Zingiberaceae family are rich sources of bioactive phytochemicals and therefore, are major targets for discovering new phytomedicines. Three of these phytochemicals, namely, flavokawain B (FB), pinostrobin (PS) and 6-shogaol (6S) have shown various therapeutic properties including antioxidant, anticarcinogenic, anti-inflammatory and antimicrobial activities. The interactions of these compounds with the main in vivo drug carrier, human serum albumin (HSA) were investigated using a multitude of spectroscopic methods, supported by molecular docking studies. Significant quenching of HSA fluorescence intensity was observed upon titration of the protein with these compounds. Analysis of the fluorescence data revealed the involvement of static quenching phenomena in these interactions, thus suggesting the formation of ligand–HSA complexes. The association constants, Ka of these ligand–HSA systems were found to lie in the range, 0.63–1.03 × 105 M−1 at 25 °C, characteristic of moderate affinity binding. Thermodynamic analysis of the binding data showed that the binding reactions were accompanied by negative enthalpy (−ΔH) and positive entropy (+ΔS) changes, which were indicative of the involvement of hydrophobic and van der Waals forces along with hydrogen bonds in the complex formation. This was corroborated by molecular docking results depicting the formation of hydrogen bonds and identification of hydrophobic residues in the vicinity of the docked ligands. Synchronous and three-dimensional fluorescence data suggested significant change in the microenvironment around Tyr and Trp residues of HSA upon binding to these compounds. Far-UV circular dichroism results indicated relatively higher thermal stability of the protein in the presence of these ligands. Competitive drug displacement experiments along with docking simulation results suggested a clear binding preference of FB and PS for Sudlow’s site I (subdomain IIA) of HSA, while 6S was able to bind favourably to Sudlow’s site I as well as with Sudlow’s site II (subdomain IIIA).